Ground-level climate at a peatland wind farm in Scotland is affected by wind turbine operation. (22nd April 2016) - Armstrong, Alona; Burton, Ralph R; Lee, Susan E; Mobbs, Stephen; Ostle, Nicholas; Smith, Victoria; Waldron, Susan; Whitaker, Jeanette
Abstract: The global drive to produce low-carbon energy has resulted in an unprecedented deployment of onshore wind turbines, representing a significant land use change for wind energy generation with uncertain consequences for local climatic conditions and the regulation of ecosystem processes. Here, we present high-resolution data from a wind farm collected during operational and idle periods that shows the wind farm affected several measures of ground-level climate. Specifically, we discovered that operational wind turbines raised air temperature by 0.18 °C and absolute humidity (AH) by 0.03 g m −3 during the night, and increased the variability in air, surface and soil temperature throughout the diurnal cycle. Further, the microclimatic influence of turbines on air temperature and AH decreased logarithmically with distance from the nearest turbine. These effects on ground-level microclimate, including soil temperature, have uncertain implications for biogeochemical processes and ecosystem carbon cycling, including soil carbon stocks. Consequently, understanding needs to be improved to determine the overall carbon balance of wind energy.